Structure and function of molecular machines involved in deadenylation-dependent 5′-3′ mRNA degradation - Zhao, Qi; Pavanello, Lorenzo; Bartlam, Mark; Winkler, Gerlof Sebastiaan (Frontiers in Genetics, 2023)
In eukaryotic cells, the synthesis, processing, and degradation of mRNA are important processes required for the accurate execution of gene expression programmes. Fully processed cytoplasmic mRNA is characterised by the presence of a 5′ cap structure and 3′ poly(A) tail. These elements promote translation and prevent non-specific degradation. Degradation via the deadenylation-dependent 5′-3′ degradation pathway can be induced by trans-acting factors binding the mRNA, such as RNA-binding proteins recognising sequence elements and the miRNA-induced repression complex. These factors recruit the core mRNA degradation machinery that carries out the following steps: (i) shortening of the poly(A) tail by the Ccr4-Not and Pan2-Pan3 poly(A)-specific nucleases (deadenylases); (ii) removal of the 5′ cap structure by the Dcp1-Dcp2 decapping complex that is recruited by the Lsm1-7-Pat1 complex; and (iii) degradation of the mRNA body by the 5′-3′ exoribonuclease Xrn1. In this review, the biochemical function of the nucleases and accessory proteins involved in deadenylation-dependent mRNA degradation will be reviewed with a particular focus on structural aspects of the proteins and enzymes involved.